FTIR and Laser Raman Spectra, Vibrational Assignments and AB-initio Calculations of 6-Hydroxypurine - Krishnakumar, V.; Ramaswamy, R.; Natarajan, A. (Asian Journal of Chemistry, 2010)
The FTIR and Raman spectra of 6-hydroxypurine were recorded and all the 36 (25a' + 11a") normal modes of vibrations are assigned assuming Cs point group symmetry. A complete vibrational analysis is proposed based on predictions from ab-initio 3-21G calculations. The vibrational assignments are supported by potential energy distribution (PED) calculations.